2006
DOI: 10.1051/ita:2006008
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous recognizable two-dimensional languages

Abstract: We consider the family UREC of unambiguous recognizable two-dimensional languages. We prove that there are recognizable languages that are inherently ambiguous, that is UREC family is a proper subclass of REC family. The result is obtained by showing a necessary condition for unambiguous recognizable languages. Further UREC family coincides with the class of picture languages defined by unambiguous 2OTA and it strictly contains its deterministic counterpart. Some closure and non-closure properties of UREC are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…UREC is the class of all unambiguous languages. It is known that UREC ⊂ REC and that it is undecidable whether a tiling system is unambiguous [3].…”
Section: Tiling Recognizable Picture Languagesmentioning
confidence: 99%
“…UREC is the class of all unambiguous languages. It is known that UREC ⊂ REC and that it is undecidable whether a tiling system is unambiguous [3].…”
Section: Tiling Recognizable Picture Languagesmentioning
confidence: 99%
“…There, Giammarresi and Restivo also posed the conjecture that unambiguous languages are properly included in the family of recognizable languages. This conjecture was solved very recently in [1], where the authors showed that unlike with words, there exist recognizable picture languages that are inherently ambiguous, i.e. not computable by unambiguous 2OTA; moreover, the problem whether a tiling system is unambiguous is undecidable.…”
Section: Introductionmentioning
confidence: 93%
“…Tiles are pictures of size (2, 2) and dominoes have size (1,2) or (2, 1). For a picture p, we denote by T ( p) (respectively D( p)) the set of all sub-tiles (respectively sub-dominoes) of p. A language L ⊆ Γ ++ is local (respectively hv-local) if there exists a set Θ of tiles (respectively dominoes) over Γ .…”
Section: Tile-local and Hv-local Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For p ∈ Σ +,+ let p be the set of subpictures of size (2,2) of p. 5 In the sequel the concepts of tile, and local language are central.…”
Section: Labeled Wang Tiles and Tiling Systemsmentioning
confidence: 99%